Outcomes associated with dentists’ risk assessment - Rindal DB, Rush WA, Perrin NA, Maupome´ G, Bader JD. (Blackwell Synergy, 2006)
To examine retrospectively the caries-related restorative experience of at-risk individuals who received fluoride-based preventive interventions to determine if the intervention resulted in fewer caries-related procedures.